Performance evaluation of N-photovoltaic thermal (PVT) water collectors partially covered by photovoltaic module connected in series: An experimental study. (September 2016) - Shyam,; Tiwari, G.N.; Fischer, Olivier; Mishra, R.K.; Al-Helal, I.M.
Highlights: Experimental validation of electrical efficiency PVT water collector has been done. Annual performance has been studied considering all types of weather conditions. Carbon credit earned in a year and annualized uniform cost has been determined. Abstract: In present communication, an experimental study has been carried out to evaluate the performance of series connected photovoltaic thermal (PVT) water collector in terms of overall thermal energy gain and overall exergy gain. Earlier developed theoretical model has been validated by performing the experiment in a clear sky day, hazy day and partially cloudy day for New Delhi climatic condition. It was found that theoretical results were in good agreement with experimental results. The annual energy gain, exergy gains, CO2 mitigation, energy matrices and carbon credit of the system have also been discussed. The energy pay-back time was found to be 1.50 and 14.19 years on overall thermal energy and exergy basis respectively. Carbon credits earned in a year were Rs. 6321.70 for overall thermal energy gain and Rs. 667.30 for overall exergy gain. For 30 years of life time, cost of one unit of electricity was estimated to be Rs. 1.53 on overall thermal energy basis however it was Rs. 14.45 on overall exergy basis.